2017
DOI: 10.1108/dpm-06-2016-0125
|View full text |Cite
|
Sign up to set email alerts
|

Information disclosure in an environmental emergency

Abstract: Purpose The purpose of this paper is to analyze the demands of the core stakeholders and how these stakeholders drive the information disclosure behaviors of the enterprise and local government. Design/methodology/approach Content analysis was conducted. The authors collected and analyzed information disclosure laws and regulations regarding environmental emergencies in China, as well as related media reports and official accident investigation report about the oil pipeline leakage and explosion accident in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
0
11
0
1
Order By: Relevance
“…According to Baidu News' official description, its news sources include more than 500 news agencies, covering a variety of Internet news sites and channels. Following Li, Ruan, Shao, and Huang (), a keyword search is performed using the Baidu News search engine. As this study examines whether the disclosure of environmental information has been used as a self‐serving tool, the keywords pertain to environmental information and include “environment,” “environmental protection,” “afforest,” “low carbon,” “pollution,” and “environmental destruction.” The specific methods are as follows.…”
Section: Methodsmentioning
confidence: 99%
“…According to Baidu News' official description, its news sources include more than 500 news agencies, covering a variety of Internet news sites and channels. Following Li, Ruan, Shao, and Huang (), a keyword search is performed using the Baidu News search engine. As this study examines whether the disclosure of environmental information has been used as a self‐serving tool, the keywords pertain to environmental information and include “environment,” “environmental protection,” “afforest,” “low carbon,” “pollution,” and “environmental destruction.” The specific methods are as follows.…”
Section: Methodsmentioning
confidence: 99%
“…Media coverage is measured by the number of articles on news websites concerning environmental issues. Following the researcher, a keyword search is performed using the Baidu News search engine [65]. The keywords pertain to environmental information and include "environment", "environmental protection", "low carbon", "pollution", and "environmental destruction".…”
Section: Measurement Of Explanatory Variables and Control Variablesmentioning
confidence: 99%
“…Both theories mainly emphasize that practices related to the government's full disclosure are influenced by the characteristics of the environment and the particular structure of each organization, mainly including technological development, political commitment among voters, corruption levels, and the demand for legal information [5], and ignore the roles of stakeholders at the micro level. Accordingly, stakeholder theory is often used as a mainstream theory to explore the internal mechanisms of information disclosure by the government [16,17]. For example, Li et al showed that the level of information disclosure is significantly affected by stakeholders' demands, including governments, social media, and environmental organizations [17].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, stakeholder theory is often used as a mainstream theory to explore the internal mechanisms of information disclosure by the government [16,17]. For example, Li et al showed that the level of information disclosure is significantly affected by stakeholders' demands, including governments, social media, and environmental organizations [17]. However, during environmental incidents, especially in China, it is usually up to local governments to decide whether or not to disclose the information, which means that stakeholder theory may fail to serve as a cornerstone to explain the phenomena [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation